2004
DOI: 10.1128/jcm.42.1.179-185.2004
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Bacillus anthracis gyrA Gene by Using a Minor Groove Binder Probe

Abstract: Identification of chromosomal markers for rapid detection of Bacillus anthracis is difficult because significant chromosomal homology exists among B. anthracis, Bacillus cereus, and Bacillus thuringiensis. We evaluated the bacterial gyrA gene as a potential chromosomal marker for B. anthracis. A real-time PCR assay was developed for the detection of B. anthracis. After analysis of the unique nucleotide sequence of the B. anthracis gyrA gene, a fluorescent 3' minor groove binding probe was tested with 171 organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
70
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 58 publications
(42 reference statements)
0
70
0
Order By: Relevance
“…One possibility for this failure is that variants other than the 49 strains of B. cereus and B. thuringiensis (testing reported in the original publication) were encountered (11 ). Another explanation is that the large amount of starting material present in boil preps may cause nonspecific amplification to occur, an explanation we consider unlikely, because gel images of the PCR product show that the samples that caused the most false positives (circled in Fig.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…One possibility for this failure is that variants other than the 49 strains of B. cereus and B. thuringiensis (testing reported in the original publication) were encountered (11 ). Another explanation is that the large amount of starting material present in boil preps may cause nonspecific amplification to occur, an explanation we consider unlikely, because gel images of the PCR product show that the samples that caused the most false positives (circled in Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Accordingly, a chromosomal assay may augment the ability to distinguish B. anthracis from other environmental Bacillus isolates, but unfortunately there are few specific chromosomal targets to differentiate B. anthracis from other Bacillus species. Until now, the gyrA sequence in B. anthracis has appeared to be unique; however, the singlebase mutation present in near neighbors has proved difficult to reliably reject even after 6 TaqMan-MGB probe designs (11 ). Although TaqMan-MGB has been used with greater success in the gyrA assay at an annealing temperature of 67°C, this temperature departs from our standard protocol, precluding the option of multiplexing this chromosomal assay with virulence plasmid genes, and still reported 7 false positives out of 29 samples.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Finally, a few single nucleotide polymorphisms (SNP) have also been considered for PCR markers. Target genes include rpoB, 24,[48][49][50][51] gyrA, 25,52,53 gyrB, 54,55 plc, 20,23,53,56 purA, 57 and the 16S-23S rDNA internal spacer sequences. [58][59][60] But, so far, only the nonsense mutation in the global regulator PlcR, which controls the transcription of secreted virulence factors in B. cereus and B. thuringiensis, have proved to be truly unique to B. anthracis strains.…”
Section: Literature Survey Of Pcr-based Detection Methodsmentioning
confidence: 99%
“…16,20,59 False-positive signals have sometimes been recorded with closely related strains of the B. cereus group using the other published SNPs. 24,49,52,59,[61][62][63] In silico analysis About a hundred sequences corresponding to all primers and probes currently published were compiled and compared using the primer alignment function of the Gegenees software (www. gegenees.org).…”
Section: Literature Survey Of Pcr-based Detection Methodsmentioning
confidence: 99%
“…Recent work by repetitive PCR has shown that the previously listed species of Bacillus, as well as Bacillus mycoides, Bacillus pseudomycoides, and Bacillus weihenstephanensis, do have some genetic differences (3). Real-time PCR assays based on the chromosomal rpoB and gyrA genes of B. anthracis have been developed (5,13,25). However, these assays are based on single-nucleotide differences between B. anthracis and other Bacillus species.…”
mentioning
confidence: 99%